2016
DOI: 10.1155/2016/8359251
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Traditional Chinese Medicine in Xerostomia and Quality of Life during Radiotherapy for Head and Neck Cancer: A Prospective Pilot Study

Abstract: Xerostomia is one of the most common acute and late complications of radiotherapy for head and neck cancer, and it affects quality of life. We conducted a prospective study to evaluate the efficacy of traditional Chinese medicine (TCM) in toxicities and quality of life during radiotherapy. Head and neck cancer patients who were scheduled for radiotherapy were checked for inclusion/exclusion criteria before enrollment. Patients in the study group (inpatients) were hospitalized in a Chinese medicine ward and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
(33 reference statements)
1
16
0
Order By: Relevance
“… 46 A previous study in Taiwan showed that policy makers resist recommendation of TCM, because they were educated as Western medical practitioners or under the modern Western medicine paradigm. 47 However, an increasing number of medical centers in Taiwan employ an integrative approach to cancer treatment, in outpatient 48 and inpatient 49 settings, in an effort to better meet the needs of cancer patients. This could improve communication among patients, TCM practitioners, and oncologists.…”
Section: Discussionmentioning
confidence: 99%
“… 46 A previous study in Taiwan showed that policy makers resist recommendation of TCM, because they were educated as Western medical practitioners or under the modern Western medicine paradigm. 47 However, an increasing number of medical centers in Taiwan employ an integrative approach to cancer treatment, in outpatient 48 and inpatient 49 settings, in an effort to better meet the needs of cancer patients. This could improve communication among patients, TCM practitioners, and oncologists.…”
Section: Discussionmentioning
confidence: 99%
“…Xerostomia is the most common oral complication of RT when the irradiated area involves the oral and maxillofacial complex, which may occur both during or after radiotherapy (4,5). Radiation-induced xerostomia depends on the cumulative doses of radiation on the head and neck region, in the first week of conventional RT, salivary flow decreases from 50 to 60%, after 7 weeks it diminishes to approximately 20% and continues to decline for up to several months after RT (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy is reduced due to the radioresistance of some cancer cells (Liu, Duo, & Duan, 2018; Zhang et al., 2017). Recently, the radiotherapy combines with traditional Chinese Medicine has been widely used for the treatment of tumor, which has a good clinical effect (Hsu et al., 2016; Zhang, Chen, Luo, Ren, & Qiao, 2017). In our results, we found that low‐dose allicin combined with X‐ray radiotherapy inhibits the growth, proliferation, migration, and induces apoptosis in HCT116 cell, and inhibits transplanted tumor of CT26 cells growth in vivo , which indicated that allicin could enhance the sensitivity of X‐ray radiotherapy for CRC.…”
Section: Resultsmentioning
confidence: 99%